Assessment of shock index and associated outcome in children with sepsis/septic shock at the tertiary care hospital - Gaigonglung Meiring; Medo M Kuotsu; Pinakini D Tollawala; Duyu Nobing; Avono Dominica Kulnu (Asian Journal of Medical Sciences, 2024)
Background: Shock index is the ratio of heart rate to the systolic blood pressure. The use of shock index for risk stratification or as an indicator of clinical improvement is helpful in early recognition of shock and optimizing treatment in sepsis and septic shock. Aims and Objectives: The objective of the study was to assess the shock index and associated outcome in children with sepsis/septic shock at the tertiary care hospital. Materials and Methods: A cross-sectional study was conducted among 95 patients admitted with sepsis or septic shock to the pediatric intensive care unit and pediatric wards of a tertiary center in Surat. The study was done over a period of 2 years from January 2020 to December 2021. The study was carried out after obtaining ethical approval from the Human Research Ethics Committee, GMC Surat. Through-out the study privacy and confidentiality was maintained at all cost for each participant by coding of patients data. Results: The mean age of the study population was 3.12±2.40 years, with age range from 1 month to 12 years. The gender distribution of the study population had 51.6% male and 48.4% female. On analysis of the shock index to the mortality of the patients at 0, 1, 2, 4, and 6 h after admission, the cutoff value of shock index at 1.6, 1.7, 1.7, 1.4, and 1.3 had a sensitivity of 89.4%, 84.8%, 78.8%, 82.3%, and 86.4%, with a specificity of 62.4%, 69%, 75.9%, 72.4%, and 75.9%, respectively. The cutoff values of the various age groups decrease as the ages of the patients increase. The overall survival rate in the study was 30.5% and mortality rate at 69.5%. Conclusion: The study concluded that shock index can be used in emergency for triage of critically ill patients. Shock index and mortality were higher compared to other studies as majority of the study participants were referred cases and were in critical stages of shock on admission to the tertiary care center.